Gate oxide reliability at the nanoscale evaluated by combining conductive atomic force microscopy and constant voltage stress - Erlbacher, Tobias; Yanev, Vasil C.; Rommel, Mathias; Bauer, Anton; Frey, Lothar (Journal of Vacuum Science & Technology B: Microelectronics Processing and Phenomena, 2011)
The gate oxide integrity of different thin films (silicon dioxide, silicon nitride, and hafnium oxide) was analyzed by constant voltage stress (CVS) at the nanoscale using conductive atomic force microscopy (cAFM) with the probe tip directly in contact to the dielectric layer. The results were evaluated assuming a Weibull failure distribution for the dielectrics under voltage stress, and a good fit was obtained for the measurement data. This indicates that CVS measurements at the nanoscale can be applied for inline characterization of as-deposited dielectrics without the need for gate electrodes. In addition, time-to-breakdown extracted from the CVS using cAFM was compared to data retrieved from CVS measurements using conventional current-voltage measurements on samples with gate electrodes. In particular, area scaling of CVS data over eight orders of magnitude using cAFM was performed for the first time. The evaluation indicates a decent match between macroscopic and nanoscale CVS measurements for the hafnium oxide and silicon dioxide samples. In contrast, significant discrepancies are evident for the silicon nitride samples, which may be related to charge trapping effect